Lithium slag-based anti-crack waterproof agent and preparation method thereof
By using lithium slag-based crack-resistant waterproofing agent, the problem of concrete cracking and waterproofing through the synergistic effect of modified lithium slag and other components is solved, and excellent crack resistance and waterproofing effect is achieved. It also has self-repair function, which improves the durability of concrete.
Patent Information
- Application Number
- CN202411849457.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-18
AI Technical Summary
In the prior art, the problem of concrete cracking has not been effectively solved, and the waterproofing agent is high, the waterproofing effect is unclear, and the self-repairing performance of cracks is limited.
Li-slag-based crack-resistant waterproofing agent is used, which consists of modified lithium slag, hydrophobic agent, calcium ion compensator, complexing agent, precipitation components and expandable graphite. The lithium slag is treated by hydrophobic modification to increase its hydrophobicity, and the multi-stage compensation shrinkage and self-healing functions are achieved through components such as calcium ion compensator.
It has achieved a multi-stage targeted reduction of concrete shrinkage cracks, improved the seepage resistance and waterproofing effect of concrete, and has self-repair function, extending the service life of concrete.
Smart Images

Figure BDA0005190857530000021 
Figure BDA0005190857530000022 
Figure BDA0005190857530000081
Abstract
Description
Technical Field
[0001] The invention relates to a lithium slag-based anti-cracking waterproof agent and a preparation method thereof, and belongs to the technical field of building materials such as cement and concrete. Background Art
[0002] Concrete cracking has always been a common problem in the engineering industry. According to the causes of cracks, 5% to 10% are structural cracks, which are mainly caused by direct stress from external loads (static and dynamic loads) and cracks caused by structural secondary stress; more than 80% of cracks are caused by deformation, such as plastic shrinkage, autogenous shrinkage, drying shrinkage caused by humidity changes, and thermal shrinkage caused by temperature changes. Once the concrete structure is damaged, external corrosive media will quickly enter the concrete through the cracks, causing the concrete structure to deteriorate and affecting its service life.
[0003] A Chinese patent application with publication number CN101327926A discloses a method for preparing low-temperature expandable graphite. The main steps of the preparation method are: immersing flake graphite in a solution mainly composed of an oxidant and an intercalation agent to perform an intercalation reaction, filtering, and replacing the intercalation agent between graphite layers with the obtained solid phase by a water exchange method. The solid phase obtained by drying is the target product. The Chinese patent application with publication number CN116283018A discloses a concrete waterproofing agent and a preparation method thereof. The raw materials and weight proportions of the waterproofing agent are as follows: 20-60 parts of calcium oxide, 15-30 parts of potassium aluminum sulfate, 5-25 parts of magnesium oxide, 5-15 parts of super absorbent resin, 10-20 parts of hydrophobic component, 40-60 parts of hydrophobic fine silica aerogel powder, 10-15 parts of sodium silicate, 8-16 parts of disodium ethylenediaminetetraacetate, 8-16 parts of glycine, 6-15 parts of lithium magnesium silicate, 150-200 parts of fly ash, 20-60 parts of silica ash, and 1-3 parts of water reducer.
[0004] The expandable graphite involved in the above patent application has an initial expansion temperature of 160°C, which is not suitable for concrete; the waterproofing agent involved has problems such as high cost, inability to alleviate concrete cracking, limited improvement in the self-healing performance of cracks, and unclear long-term waterproofing effect. Summary of the invention
[0005] In order to overcome the defects of the prior art, one of the objects of the present invention is to provide a lithium slag-based anti-cracking waterproofing agent, which has excellent anti-cracking performance and waterproofing effect, and at the same time has multi-stage shrinkage compensation function and self-repair function.
[0006] The second object of the present invention is to provide a method for preparing a lithium slag-based anti-cracking waterproofing agent.
[0007] To achieve the purpose of the present invention, the following technical solutions are provided.
[0008] A lithium slag-based anti-cracking waterproof agent, taking the total mass of the lithium slag-based anti-cracking waterproof agent raw material as 100%, wherein the components and their mass fractions are:
[0009]
[0010] Preferably, a lithium slag-based anti-cracking waterproofing agent, taking the total mass of the lithium slag-based anti-cracking waterproofing agent raw material as 100%, wherein the components and their mass fractions are:
[0011]
[0012] The modified lithium slag is prepared by the following method:
[0013] Spray a water repellent on the surface of the lithium slag, mix well, leave it for 1 day and then dry it to obtain modified lithium slag.
[0014] Lithium slag is usually industrial residue produced after lithium is extracted from lepidolite, spodumene and salt lake brine. The lithium slag described in the present invention is industrial residue produced by producing lithium carbonate by sulfuric acid method after calcining spodumene at a high temperature of 1000°C to 1200°C. Taking the total mass of lithium slag as 100%, sulfite ion (SO3 2- ) mass fraction ≥ 15%; preferably SO3 2- The mass fraction is 15% to 25%.
[0015] The hydrophobic agent is an organic silicon material, which can change the surface characteristics of the material, prevent the material capillaries and pores from absorbing water, greatly reduce the water absorption rate of the substrate, and provide the material with excellent hydrophobic properties. Preferably, the hydrophobic agent is one or more of n-octyltriethoxysilane, polymethyltriethoxysilane and triethoxyoctylsilane; more preferably, the hydrophobic agent is n-octyltriethoxysilane, with a purity of ≥97%, a density of 0.88 g / ml, and a molecular weight of 276.49.
[0016] Preferably, based on the total mass of the lithium slag being 100%, the amount of the water repellent used is 0.8% to 1.2% of the mass of the lithium slag.
[0017] The calcium ion compensator is one or more of calcium formate, calcium hydroxide, calcium nitrite and calcium dodecylbenzene sulfonate. Preferably, the calcium ion compensator comprises calcium formate and calcium hydroxide, and the mass ratio of calcium formate to calcium hydroxide is 1:5-15. The calcium formate content is ≥98%, the pH value (25°C) is 6.5-8.0, and the density is 2.02-2.03 g / cm 3 ; Calcium hydroxide fineness ≥325 mesh, content ≥97%.
[0018] The complexing agent is one or more of ethylenediaminetetraacetic acid (EDTA), sodium citrate, tartaric acid and sorbitol; preferably, the complexing agent includes ethylenediaminetetraacetic acid and sodium citrate, and the mass ratio of EDTA to sodium citrate is 1:0.1-0.3. EDTA is a white crystalline powder, with a content of ≥99% and a molecular weight of 292.24; sodium citrate is a white crystalline powder, with a content of ≥99% and a molecular weight of 294.10.
[0019] The precipitation component grows insoluble crystals by reacting with the calcium ion compensator, plugging the capillary pores and microcracks of the concrete matrix, thereby improving the waterproof and anti-seepage ability of the concrete. Preferably, the precipitation component is one or more of sodium carbonate, potassium carbonate and sodium bicarbonate; more preferably, the precipitation component is sodium carbonate carbon, with a fineness of ≥200 mesh, a content of ≥99%, and a molecular weight of 105.99.
[0020] Preferably, the mass ratio of the calcium ion compensator, the complexing agent and the precipitation component is 1:0.4-0.6:0.6-1.
[0021] The initial expansion temperature of the expandable graphite is 60° C. Preferably, the expansion volume of the expandable graphite is 100 mL / g to 300 mL / g.
[0022] A method for preparing the lithium slag-based anti-cracking waterproofing agent according to the present invention, the method comprises the following steps:
[0023] The raw material components are weighed according to mass fraction, mixed evenly, and dry-milled to obtain a powder which is a lithium slag-based anti-cracking waterproofing agent.
[0024] Preferably, the specific surface area of the powder obtained after dry ball milling is 300 m 2 / kg~450m 2 / kg.
[0025] Beneficial Effects
[0026] (1) The present invention provides a lithium slag-based anti-cracking waterproofing agent, which can reduce concrete shrinkage cracks in a targeted manner in multiple stages, and at the same time can make the concrete surface have a larger contact angle so that the concrete has excellent anti-seepage performance and waterproof effect; during the service stage of the concrete, the cracked parts can be self-repaired, thereby improving the durability of the concrete.
[0027] (2) The present invention provides a lithium slag-based anti-cracking waterproofing agent, wherein the modified lithium slag is obtained by being treated with a hydrophobic agent. Since lithium slag has a porous structure and is easy to absorb water, which will affect the workability of the concrete mixture, the present invention breaks through the process of spraying a hydrophobic agent on its surface for hydrophobic modification. The surface of the modified lithium slag has hydrophobicity, which can reduce the impact on the workability of the mixture. Combined with its own porous structure, it can be used as a "water storage container" to provide a water source for subsequent hydration reactions, which can greatly improve the pore structure of concrete and increase the density of concrete. At the same time, it can reduce water evaporation in the plastic stage of concrete and specifically reduce plastic shrinkage cracks. In addition, it can also increase the contact angle of the concrete surface in the later stage to prevent water from penetrating and achieve an excellent waterproof effect.
[0028] (3) The present invention provides a lithium slag-based anti-cracking waterproofing agent, wherein the lithium slag contains sulfite ions (SO3 2- ), during the concrete hardening stage, SO3 in lithium slag 2- It can promote the formation of insoluble crystalline calcium aluminate, causing the volume expansion of concrete, compensating for the shrinkage of concrete during the hardening stage, specifically reducing shrinkage cracks, and has a self-repairing function. SO3 2- The mass fraction of SO3 is greater than or equal to 15%, which can ensure that there are enough sulfite ions to participate in the expansion reaction; further, in order to avoid excessive expansion and cracking caused by excessive sulfite ions, the SO3 2- The mass fraction of lithium slag should not exceed 25%; the volcanic ash effect of lithium slag can also be used to improve the density of concrete, thereby improving the durability of concrete.
[0029] (4) The present invention provides a lithium slag-based anti-cracking waterproofing agent, in which expandable graphite with an initial expansion temperature of 60°C is used, which can produce volume expansion during the temperature rise stage of concrete, generate internal prestress to the concrete, and reduce thermal shrinkage cracks of the concrete; the higher the initial expansion temperature exceeds 60°C, the less effective it is in controlling concrete cracking.
[0030] (5) The present invention provides a lithium slag-based anti-cracking waterproofing agent, in which a calcium ion compensator, a complexing agent and a precipitation component can synergistically generate insoluble crystals, thereby improving the density of concrete and repairing cracks. When water enters the concrete through cracks, the complexing agent and the Ca in the calcium ion compensator react to form insoluble crystals. 2+ A complex reaction occurs to generate a water-soluble but unstable calcium complex. The calcium complex reacts with SO3 in the modified lithium slag. 2- , precipitation components and CO3 in concrete 2- 、HCO3 2- 、SiO3 2-The replacement precipitation reaction occurs, generating insoluble precipitates, while repairing the cracks, the complexing agent is released and continues to be transported to the interior of the concrete and combined with Ca 2+ The complexation reaction is repeated to generate calcium complex, and the complexation-release-re-complexation-re-release reaction occurs continuously, so that the waterproofing agent has the function of self-repairing for a long time.
[0031] (6) The present invention provides a lithium slag-based anti-cracking waterproofing agent, in which zirconium silicone can promote the hydration of unhydrated cement, promote the formation of calcium hydroxide, improve the density of concrete, and provide calcium ions for the formation of insoluble crystals; zirconium silicone and modified lithium slag work together to further enhance the expansion and hydration reaction capabilities of lithium slag.
[0032] (7) The present invention provides a method for preparing a lithium slag-based anti-cracking waterproofing agent, which is simple and easy to operate, wherein the specific surface area of the powder obtained after dry ball milling is preferably 300 m 2 / kg~450m 2 / kg; because the specific surface area is less than 300m 2 / kg, it has a greater negative impact on the working performance of the mixture. When the specific surface area is greater than 450m 2 / kg, the internal pore structure is destroyed and it cannot act as a "water storage container" to provide water for subsequent hydration reactions. It cannot improve the pore structure of concrete and has a poor effect on the compaction of concrete. DETAILED DESCRIPTION
[0033] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention.
[0034] In the following examples and comparative examples:
[0035] Lithium slag is the industrial residue produced by producing lithium carbonate using the sulfuric acid method after spodumene is calcined at a high temperature of 1000℃~1200℃;
[0036] The fineness of calcium hydroxide is 400 mesh;
[0037] The fineness of sodium carbonate is 230 mesh.
[0038] Example 1
[0039] A lithium slag-based anti-cracking waterproof agent, taking the total mass of the lithium slag-based anti-cracking waterproof agent raw material as 100%, wherein the components and their mass fractions are:
[0040] Modified lithium slag 43.2%, calcium formate 2.5%, calcium hydroxide 22.8%, EDTA 11.4%, sodium citrate 1.3%, sodium carbonate 16.9%, zirconium silicone 1.7%, expandable graphite 0.2%.
[0041] The modified lithium slag is prepared by the following method:
[0042] Spray the water repellent n-octyltriethoxysilane on the surface of lithium slag, mix well, leave for 1 day and then dry to obtain modified lithium slag; based on the total mass of lithium slag as 100%, the amount of water repellent is 0.9% of the mass of lithium slag, and SO3 2- The mass fraction is 22%.
[0043] The initial expansion temperature of expandable graphite is 60°C and the expansion volume is 240 mL / g.
[0044] A method for preparing the lithium slag-based anti-cracking waterproofing agent described in this embodiment, the method steps are as follows:
[0045] The raw material components were weighed according to the mass fraction, mixed evenly, and dry-milled for 5 min to obtain a specific surface area of 419 m 2 / kg powder, which is a lithium slag based anti-cracking and waterproofing agent.
[0046] Example 2
[0047] A lithium slag-based anti-cracking waterproof agent, taking the total mass of the lithium slag-based anti-cracking waterproof agent raw material as 100%, wherein the components and their mass fractions are:
[0048] Modified lithium slag 55%, calcium formate 3.4%, calcium hydroxide 17.2%, EDTA 8.8%, sodium citrate 1.1%, sodium carbonate 13.4%, zirconium silicone 1%, expandable graphite 0.1%.
[0049] The modified lithium slag is prepared by the following method:
[0050] Spray the water repellent n-octyltriethoxysilane on the surface of lithium slag, mix well, leave for 1 day and then dry to obtain modified lithium slag; based on the total mass of lithium slag as 100%, the amount of water repellent is 1.2% of the mass of lithium slag, and SO3 2- The mass fraction is 25%.
[0051] The initial expansion temperature of expandable graphite is 60°C and the expansion volume is 300 mL / g.
[0052] A method for preparing the lithium slag-based anti-cracking waterproofing agent described in this embodiment, the method steps are as follows:
[0053] The raw material components were weighed according to the mass fraction, mixed evenly, and dry-milled for 5 minutes to obtain a specific surface area of 450m 2 / kg powder, which is a lithium slag based anti-cracking and waterproofing agent.
[0054] Example 3
[0055] A lithium slag-based anti-cracking waterproof agent, taking the total mass of the lithium slag-based anti-cracking waterproof agent raw material as 100%, wherein the components and their mass fractions are:
[0056] Modified lithium slag 40%, calcium formate 1.4%, calcium hydroxide 20%, EDTA 9.8%, sodium citrate 2.8%, sodium carbonate 20.9%, zirconium silicone 4.8%, expandable graphite 0.3%.
[0057] The modified lithium slag is prepared by the following method:
[0058] Spray the water repellent n-octyltriethoxysilane on the surface of lithium slag, mix well, leave for 1 day and then dry to obtain modified lithium slag; based on the total mass of lithium slag as 100%, the amount of water repellent is 0.8% of the mass of lithium slag, SO3 2- The mass fraction is 15%.
[0059] The initial expansion temperature of expandable graphite is 60°C and the expansion volume is 100 mL / g.
[0060] A method for preparing the lithium slag-based anti-cracking waterproofing agent described in this embodiment, the method steps are as follows:
[0061] The raw material components were weighed according to mass fraction, mixed evenly, and dry-milled for 5 min to obtain a specific surface area of 300 m 2 / kg powder, which is a lithium slag based anti-cracking and waterproofing agent.
[0062] Comparative Example 1
[0063] A lithium slag-based waterproofing agent, wherein the total mass of the lithium slag-based waterproofing agent raw material is 100%, wherein the components and their mass fractions are:
[0064] Lithium slag 43.2%, calcium formate 2.5%, calcium hydroxide 22.8%, EDTA 11.4%, sodium citrate 1.3%, sodium carbonate 16.9%, zirconium silicone 1.7%, expandable graphite 0.2%.
[0065] Taking the total mass of lithium slag as 100%, SO3 2- The mass fraction is 22%.
[0066] The initial expansion temperature of expandable graphite is 60°C and the expansion volume is 240 mL / g.
[0067] A method for preparing the lithium slag-based waterproofing agent described in this comparative example, the method steps are as follows:
[0068] The raw material components were weighed according to the mass fraction, mixed evenly, and dry-milled for 5 minutes to obtain a specific surface area of 422m 2 / kg powder, which is a lithium slag based waterproofing agent.
[0069] Comparative Example 2
[0070] A lithium slag-based waterproofing agent, wherein the total mass of the lithium slag-based waterproofing agent raw material is 100%, wherein the components and their mass fractions are:
[0071] Modified lithium slag 43.4%, calcium formate 2.5%, calcium hydroxide 22.8%, EDTA 11.4%, sodium citrate 1.3%, sodium carbonate 16.9%, zirconium silicone 1.7%.
[0072] The modified lithium slag is prepared by the following method:
[0073] Spray the water repellent n-octyltriethoxysilane on the surface of lithium slag, mix well, leave for 1 day and then dry to obtain modified lithium slag; based on the total mass of lithium slag as 100%, the amount of water repellent is 0.9% of the mass of lithium slag, and SO3 2- The mass fraction is 22%.
[0074] A method for preparing the lithium slag-based waterproofing agent described in this comparative example, the method steps are as follows:
[0075] The raw material components were weighed according to mass fraction, mixed evenly, and dry-milled for 5 min to obtain a specific surface area of 417 m 2 / kg powder, which is a lithium slag based waterproofing agent.
[0076] Comparative Example 3
[0077] A lithium slag-based anti-cracking waterproof agent, taking the total mass of the lithium slag-based anti-cracking waterproof agent raw material as 100%, wherein the components and their mass fractions are:
[0078] Modified lithium slag 43.2%, calcium formate 2.5%, calcium hydroxide 22.8%, EDTA 11.4%, sodium citrate 1.3%, sodium carbonate 16.9%, zirconium silicone 1.7%, expandable graphite 0.2%.
[0079] The modified lithium slag is prepared by the following method:
[0080] Spray the water repellent n-octyltriethoxysilane on the surface of lithium slag, mix well, leave for 1 day and then dry to obtain modified lithium slag; based on the total mass of lithium slag as 100%, the amount of water repellent is 0.9% of the mass of lithium slag, and SO3 2- The mass fraction is 6.3%.
[0081] The initial expansion temperature of expandable graphite is 60°C and the expansion volume is 240 mL / g.
[0082] A method for preparing the lithium slag-based anti-cracking waterproofing agent described in this comparative example, the method steps are as follows:
[0083] The raw material components were weighed according to the mass fraction, mixed evenly, and dry-milled for 5 minutes to obtain a specific surface area of 420 m 2 / kg powder, which is a lithium slag based anti-cracking and waterproofing agent.
[0084] Test experiment
[0085] The waterproofing agents prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were added to the mortar in the form of internal mixing, replacing cement in equal amounts, with a mass fraction of 1%. The specific experimental group ratios are shown in Table 1; the mortar was formed according to the proportions in Table 1, and the concrete water absorption ratio and shrinkage ratio were tested with reference to JC474-2008 "Mortar Concrete Waterproofing Agent". Concrete was formed according to the proportions in Table 2, the slump was tested, and the concrete cracking temperature was tested by a temperature stress testing machine, and the test results are shown in Table 3.
[0086] Table 1 Mortar test ratio
[0087] Cement / g Standard sand / g Water / g Waterproofing agent / g 1336.5 4050 675 13.5
[0088] Table 2 Concrete experimental mix ratio
[0089]
[0090] Table 3 Performance test results of embodiments and comparative examples
[0091]
[0092] From the test data in Table 3, it can be seen that in Comparative Example 1, since the hydrophobic agent n-octyltriethoxysilane was not used to hydrophobically modify the lithium slag, the water absorption ratio of the concrete was greatly improved. The unmodified lithium slag had an adverse effect on the performance of the mixture, which was manifested as a decrease in slump and the inability to reduce the evaporation of water in the plastic stage, which was manifested as a larger shrinkage ratio; Comparative Example 2 lacked expandable graphite, so during the temperature stress test, it could not generate sufficient pre-compression stress to reduce the risk of cracking in the concrete temperature rise stage, which was manifested as a larger cracking temperature in Comparative Example 2 than in Example 1; SO3 in the lithium slag of Comparative Example 3 2- The mass fraction is only 6.3%, which cannot produce enough expansion products in the hydration stage, which is manifested as an increase in the shrinkage ratio and a corresponding cracking temperature greater than that of the embodiment. 2- Different mass fractions are manifested as different shrinkage rates and cracking temperatures; the expansion volume of expandable graphite affects the cracking temperature, and different amounts of water-repellent agent directly affect the water absorption ratio.
[0093] Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A lithium slag-based anti-cracking waterproofing agent, characterized in that: Taking the total mass of the lithium slag-based anti-cracking waterproofing agent raw material as 100%, the components and their mass fractions are as follows: The modified lithium slag is prepared by the following method: Spraying a water repellent on the surface of the lithium slag, mixing evenly, and drying to obtain modified lithium slag; Taking the total mass of lithium slag as 100%, SO3 2- The mass fraction of ≥15%; The water repellent is a silicone material; The calcium ion compensator is one or more of calcium formate, calcium hydroxide, calcium nitrite and calcium dodecylbenzene sulfonate; The complexing agent is one or more of ethylenediaminetetraacetic acid, sodium citrate, tartaric acid and sorbitol; The precipitation component is one or more of sodium carbonate, potassium carbonate and sodium bicarbonate; The initial expansion temperature of expandable graphite is 60°C.
2. A lithium slag-based anti-cracking waterproofing agent according to claim 1, characterized in that: Taking the total mass of the lithium slag-based anti-cracking waterproofing agent raw material as 100%, the components and their mass fractions are as follows:
3. A lithium slag-based anti-cracking waterproofing agent according to claim 1 or 2, characterized in that: The calcium ion compensator comprises calcium formate and calcium hydroxide, and the mass ratio of calcium formate to calcium hydroxide is 1:5-15; The complexing agent comprises ethylenediaminetetraacetic acid and sodium citrate, and the mass ratio of ethylenediaminetetraacetic acid to sodium citrate is 1:0.1-0.3; The precipitated component is sodium carbonate carbon; The expansion volume of expandable graphite is 100 mL / g to 300 mL / g.
4. A lithium slag-based anti-cracking waterproofing agent according to claim 3, characterized in that: The mass ratio of the calcium ion compensator, the complexing agent and the precipitation component is 1:0.4-0.6:0.6-1.
5. A lithium slag-based anti-cracking waterproofing agent according to claim 1 or 2, characterized in that: Taking the total mass of lithium slag as 100%, SO3 2- The mass fraction is 15% to 25%.
6. A lithium slag-based anti-cracking waterproofing agent according to claim 1 or 2, characterized in that: The water repellent is one or more of n-octyltriethoxysilane, polymethyltriethoxysilane and triethoxyoctylsilane.
7. A lithium slag-based anti-cracking waterproofing agent according to claim 6, characterized in that: The water repellent is n-octyltriethoxysilane.
8. A lithium slag-based anti-cracking waterproofing agent according to claim 1 or 2, characterized in that: Taking the total mass of lithium slag as 100%, the dosage of the water repellent is 0.8% to 1.2% of the mass of the lithium slag.
9. A method for preparing the lithium slag-based anti-cracking waterproofing agent according to any one of claims 1 to 8, characterized in that: The raw material components are weighed according to mass fraction, mixed evenly, and dry-milled to obtain a powder which is a lithium slag-based anti-cracking waterproofing agent.
10. The method for preparing a lithium slag-based anti-cracking waterproofing agent according to claim 9, characterized in that: The specific surface area of the powder obtained after dry ball milling is 300m 2 / kg~450m 2 / kg.
Citation Information
Patent Citations
Preparation of low temperature expandable graphite
CN101327926A
Concrete waterproof agent and preparation method thereof
CN116283018A